If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-12x+7=4x-9
We simplify the equation to the form, which is simple to understand
-12x+7=4x-9
We move all terms containing x to the left and all other terms to the right.
-12x-4x=-9-7
We simplify left and right side of the equation.
-16x=-16
We divide both sides of the equation by -16 to get x.
x=1
| 7v-9=4v+3 | | 81t^2-144t+64= | | 5(2+t)-2(t+1)= | | 6v-4=5v+4 | | 16s^2-56s+49= | | b=75+(15+6)w | | (-2xy^2)(3x^2y^4)= | | x(x+7)=120 | | v-5/3-v=-3(v-1) | | 8n-(6n+5)=7 | | 190-2x+x+10=180 | | 2x-1=y | | 2x+10=y | | 4+4x/3=6 | | 2x-13=y | | -3x+5=y | | 3x+6=33 | | 13=-3x-8 | | (3x-1)(x+4)= | | 2y-6y+8=2(-2y+9) | | 10x^2-20=-5x | | 4x+9-y= | | 10(y-3)=5(y+5) | | x^2-10x-25=36 | | 12x^2+18=30+12x | | 4x^2-40[x]+51=0 | | x^2-10x-25=6 | | x-10x-25=6 | | e(n)=2(n) | | (y-5)(5+5)= | | 8+3(6+4)= | | .5(6x+4)=x+2(x+1) |